KUALITAS PELAYANAN SEBAGAI DETERMINAN KEPUASAN PELANGGAN JASA TRANSPORTASI GRAB BIKE DI YOGYAKARTA - Fajar Ramadhan; Hendro Setyono (Universitas Ahmad Dahlan, 2019)
This research aims to analyze the influence of the quality of service of customer satisfaction on service businesses Grab-Bike transport in Yogyakarta. This research uses the five independent variables i.e. tangible, reliability, responsiveness, assurance and emphaty with one dependent variable i.e. consumer satisfaction. After a review of the literature as well as field and preparation of the hypothesis, the data in this study were collected through the dissemination of a questionnaire to 70 people who never use the Grab-Bike transport as research samples. Sampling technique used is a Non probability sampling method sampling incidental. Methods of data analysis used is the quantitative analysis that is test validity and reliability, multiple linear regression analysis, t-test and F-test as well as the coefficient of determination. Based on data analysis, the results showed that the indicators on research is valid and reliability. Hypothesis test on tangible, responsiveness, assurance and emphaty no effect significantly to consumer satisfaction. Hypothesis test of reliability has a positive and significant influence toward customer satisfaction.